2018
DOI: 10.1002/jcla.22460
|View full text |Cite
|
Sign up to set email alerts
|

Dot enzyme‐linked immunosorbent assay strip as a screening tool for detection of autoantibody to interferon gamma in sera of suspected cases of adult‐onset immunodeficiency

Abstract: This simple method provides prompt qualitative results that can be read visually and used in facilities with limited testing capabilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Patients with adult-onset immunodeficiency have been identified by characterizing defects in IFN- γ signaling, which generally involve the generation of anti-IFN- γ autoAbs and are partly due to inherited mutations in IFN- γ -signaling-associated factors [3, 4]. While the detection methodology has been demonstrated and modified [3, 22, 23], a functional neutralizing assay is lacking, although an assessment of IFN- γ -activated STAT1 is usually carried out. Our study found blockade effects of anti-IFN- γ autoAbs not only on the IFN- γ signaling pathway [14] but also on IFN- γ -driven antimicrobial activity, including M1 macrophage differentiation, antimicrobial factor production, and phagocytic activation.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with adult-onset immunodeficiency have been identified by characterizing defects in IFN- γ signaling, which generally involve the generation of anti-IFN- γ autoAbs and are partly due to inherited mutations in IFN- γ -signaling-associated factors [3, 4]. While the detection methodology has been demonstrated and modified [3, 22, 23], a functional neutralizing assay is lacking, although an assessment of IFN- γ -activated STAT1 is usually carried out. Our study found blockade effects of anti-IFN- γ autoAbs not only on the IFN- γ signaling pathway [14] but also on IFN- γ -driven antimicrobial activity, including M1 macrophage differentiation, antimicrobial factor production, and phagocytic activation.…”
Section: Discussionmentioning
confidence: 99%
“…However in addition, we would propose to take further advantage of the widely available Quantiferon assay: Addition of IFN gamma to the tuberculosis tube, if necessary in the presence or absence of a suitable costimulus such as lipopolysaccharide, should theoretically induce the production of TNF-α and IL12, which would be suppressed in the presence of nAIGA. Rattanathammethee et al [55 ▪ ] propose a simple easy to perform dot-ELISA assay which, although based on qualitative visual evaluation, shows excellent positive and negative predictive values. This test should be economical and could be performed even in remote places with limited testing capabilities.…”
Section: Detection and Functional Evaluation Of Anticytokine Autoantimentioning
confidence: 99%
“…Based on studies in Thailand and Taiwan, high-titers of anti-IFN-γ autoAb 7 are present in 81% of patients with NTM (52 patients) and 96% of patients with other opportunistic infections with or without NTM (45 patients); neutralizing activity of these autoAbs was suggested as a parameter for monitoring of disease onset and progression. Until now, detection of anti-IFN-γ autoAbs is developed 7,14 but is not widely used in clinical studies. This study aimed to measure anti-IFN-γ autoAbs in patients with NTM infection.…”
Section: Introductionmentioning
confidence: 99%